The Merck index : an encyclopedia of chemicals, drugs, and biologicals - O'Neil, Maryadele J.; Royal Society of Chemistry (United Kingdom). (Cambridge, UK : Royal Society of Chemistry, 2013)
A comprehensive reference work on organic chemistry that provides information on thousands of substances and structural formulas.
Includes bibliographical references and indexes.
Keywords: Drugs -- Dictionaries; Chemicals -- Dictionaries; Biologicals -- Dictionaries; Biomolecules -- Dictionaries; Pharmaceutical preparations; Dictionaries